Two new species of Epimelitta Bates from Brazil and a new synonymy in Stenopseustes Bates (Coleoptera, Cerambycidae, Cerambycinae, Rhinotragini) - Casari, Sônia A.; Santos-Silva, Antonio (Zootaxa, 2016)
Two new species of Epimelitta (Cerambycidae: Cerambycinae: Rhinotragini) are described from Brazil: E. prodigiosa sp. nov., from Espírito Santo, Rio de Janeiro and São Paulo and E. penicillata sp. nov., from Santa Catarina and Rio Grande do Sul. The larva and pupa of E. prodigiosa sp. nov. are also described and illustrated. Stenopseustes gibbicollis Fisher, 1947 is synonymized with S. aeger Bates, 1873.